2019
DOI: 10.3390/app9235002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Mechanical Analysis of Buried Corroded Concrete Pipes under Static Traffic Loads

Abstract: Concrete pipes are widely used in municipal drainage projects. Corrosion is a common issue affecting concrete pipes, causing leakage of pipes, environmental pollution, and road collapse. It is necessary to study the mechanical properties of corroded concrete pipes. To investigate in depth the influence of corrosion depths, corrosion widths, traffic loads, and cover depths, on mechanical characteristics of buried corroded concrete pipes under static traffic loads, a series of full-scale tests were carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…For a long time, research on soil collapse has been mainly based on the mechanical analysis of the effect of soil collapse on buried pipelines [30,31], lacking the necessary dynamic evolution process of buried pipeline collapse. Soil collapse simulation techniques mainly include three types: manual removal of collapse areas, application of displacement loads, and unit life and death techniques.…”
Section: Discussion On Soil Collapse Simulation Research Methodsmentioning
confidence: 99%
“…For a long time, research on soil collapse has been mainly based on the mechanical analysis of the effect of soil collapse on buried pipelines [30,31], lacking the necessary dynamic evolution process of buried pipeline collapse. Soil collapse simulation techniques mainly include three types: manual removal of collapse areas, application of displacement loads, and unit life and death techniques.…”
Section: Discussion On Soil Collapse Simulation Research Methodsmentioning
confidence: 99%
“…Moreover, corrosion depth has a greater impact on the pipeline than the corrosion length and corrosion width [20]. Fang et al [21] showed that as the corrosion depth increases, the maximum principal stress and strain of the pipeline also increase, and the probability of pipe failure increases. Wang et al [22] investigated the causes of cast iron pipe failure and established a new corrosion pit depth prediction model.…”
Section: B Predicting the Depth Of Corrosion In Pipelinesmentioning
confidence: 99%
“…To determine an appropriate element size, element sensitivity analysis was conducted in this section, and five element sizes were chosen for numerical calculations, as shown in Table 3. To assess the influence of the element size on the calculation results, the computed results using different element sizes were extracted and compared with the experimental data of Fang et al [27], as illustrated in Figure 5. In the figure, "C" represents the error at the crown of the pipe, "I" represents the error at the invert of the pipe, and "S" represents the error at the springline of the pipe.…”
Section: Mesh Sensitivity and Convergence Analysismentioning
confidence: 99%